Employment and foreign investment : policy options for developing countries. - LALL, Sanjaya (1995)
Notes the growing importance of foreign direct investment for growth and employment creation in developing countries, and the marked shift towards policies which welcome inflows of foreign direct investment. Argues that this calls for more than passive 'open-door' policies. Points out that it is possible to maximise the benefits and mitigate the negative effects of foreign investment through appropriate policies.